Gender and Social Structure in Madagascar - Huntington, Richard (Indiana University Press, 1988)
This is a theoretical and ethnographic essay on sexuality and the social order using the Bara material as a vehicle for demonstrating important universal features of human social life. In this sense the style of exposition and organization is modeled after some of the famous essays of the Année sociologique on issues such as bodily polarity, secondary burial, and seasonal variations, all of which drew on limited ethnographic material to pursue general features of humanity.